Assessing Pre-Service Teachers View On Improving Discipline in Colleges of Education in Ghana: A Study at Wesley College of Education - Mensah, Grace Aba; Boateng Berko, Lydia; Yeboah, Grace (International Journal of Scientific Research and Management (IJSRM), 2020)
Education at every level is expected to affect behaviour of those who experience it.  This makes discipline very essential component in delivery of education. The study was a case study designed to examine students’ views on improving discipline in Colleges of Education. Data was collected from 244 respondents at Wesley College of Education in Ashanti Region, Ghana using a 4-point Likert and 5-point Likert scale questionnaire. The data were analysed using frequency and percentage. The study revealed that students viewed the concept of discipline as punishment which was generally perceived as severe. Punishment in the College included withdrawing students’ privileges, in-school suspension and out-of-school suspension among others. They regarded the causes of indiscipline to be the result of lack of students’ participation in the decision making process of the school, unclear rules. Students’ indiscipline was also attributed to bad training at home, students falling into bad company in school and lack of freedom for students. However disciplinary measures such as the use of guidance and counselling services, religious training, and parental involvement, had more positive responses.  Based on the findings, some recommendations were made to improve discipline in Colleges of Education. For instance, there should be clarity of rules, this will enable students to understand the rules and abide by them. In addition, Students of colleges should be taught the value of self-discipline. These will help the student teacher to learn more appropriate ways to ensure discipline when they go out to practice.